2021
DOI: 10.1136/jmedgenet-2020-107510
|View full text |Cite
|
Sign up to set email alerts
|

Disentangling molecular and clinical stratification patterns in beta-galactosidase deficiency

Abstract: IntroductionThis study aims to define the phenotypic and molecular spectrum of the two clinical forms of β-galactosidase (β-GAL) deficiency, GM1-gangliosidosis and mucopolysaccharidosis IVB (Morquio disease type B, MPSIVB).MethodsClinical and genetic data of 52 probands, 47 patients with GM1-gangliosidosis and 5 patients with MPSIVB were analysed.ResultsThe clinical presentations in patients with GM1-gangliosidosis are consistent with a phenotypic continuum ranging from a severe antenatal form with hydrops fet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 32 publications
1
4
0
Order By: Relevance
“…Based on our genetic findings, we were able to compare our clinical observations with the classification used by Tebani et al, 13 and we found comparable results in association between phenotype and genotype (early‐onset <2 year corresponding to our types 1/2a patients, late‐onset >2 years to our types 2b/3 patients). Furthermore, our data suggest that the c.1733A > G variant does not appear to be associated with type 1 but repeatedly with type 2a (onset of symptoms between 6 months and 2 years).…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…Based on our genetic findings, we were able to compare our clinical observations with the classification used by Tebani et al, 13 and we found comparable results in association between phenotype and genotype (early‐onset <2 year corresponding to our types 1/2a patients, late‐onset >2 years to our types 2b/3 patients). Furthermore, our data suggest that the c.1733A > G variant does not appear to be associated with type 1 but repeatedly with type 2a (onset of symptoms between 6 months and 2 years).…”
Section: Discussionsupporting
confidence: 79%
“…Thirty‐seven variants have been previously published; 1 (c.457 + 96C > T, p.?) had not been described so far, probably leading to an alteration of splicing with creation of a splice site—according to Splicing Prediction Pipeline 9–13 . Twenty‐four variants have been identified in patients with type 1, 7 with type 2a, 4 with type 2b, and 6 with type 3.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Odontoid hypoplasia, as observed in all late infantile patients but not juvenile patients, requires cervical spine evaluation in late infantile patients prior to anesthesia, and anesthetic care FIGURE 2 | Genotypes in GM1 gangliosidosis. Schematic representation of 261 GLB1 variants with a reported phenotype of GM1-gangliosidosis and/or Morquio B registered in the database HGMD (2021) updated with the novel variants from Tebani et al (2021). The GLB1 gene is located on the short arm of chromosome 3 (3p21.33).…”
Section: Clinical Manifestationsmentioning
confidence: 99%
“…Bold text represents GM1 gangliosidosis and/or Morquio B reported phenotypes. A summary of the 261 reported variants with a phenotype of GM1 gangliosidosis and/or Morquio B disease can be found at GLB1 (HGMD, 2021; Tebani et al, 2021). The main domains of the protein are shown above the exons.…”
Section: Clinical Manifestationsmentioning
confidence: 99%